A few introductory notes on the special issue on the Evaluation Framework for Promoting Gender Equality in Research and Innovation (EFFORTI). (April 2020) - Marra, Mita
Highlights: Political relevance of EFFORTI. Theoretical innovation of EFFORTI. Abstract: Being European with a long standing research interest in evaluation of gender policies, I could not begin my assignment as Editor in Chief with a better task. Readers will forgive me for these few biographical notes. Before presenting this special issue, I owe many thanks to Jonny Morell who involved me in its design as early as June 2018. I also want to thank Susanne Bührer, Clemens Striebing, Evanthia Kalpazidou Schmidt, Rachel Palmén, Sybille Reidl, Florian Holzinger and Jörg Müller, who invited me at the 2019 conference in Brussels, where the final results of the European initiative 'Evaluation Framework for Promoting Gender Equality in Research and Innovation' (EFFORTI) were critically debated. 1 And drawing on the outline and comments I pointed out on that occasion, in this short introduction, I highlight why this special issue is politically relevant and theoretically innovative.